Mapping the conceptual framework of psychological well-being among pregnant adolescents and influential factors: A scoping review - Sari, Yanti Puspita; Armi, Yeltra; Lin, Chung-Ying (Universitas Airlangga, 2025)
Introduction: Pregnancy in adolescents has the potential risk of disrupting psychological well-being. Understanding how psychological well-being is conceptualized and assessed among adolescents, as well as identifying influential factors, is essential for developing appropriate and effective interventions. This review aims to map the conceptual approaches and assessment methods used to evaluate psychological well-being among pregnant adolescents and to identify influential factors associated with psychological well-being during pregnancy. Methods: The study procedures were carried out using a scoping review that followed the Joanna Briggs Institute approach. Literature searches included terms from Emtree, MeSH, and CINAHL headings across 5 databases, including Embase, Medline (Ovid), CINAHL, Cochrane, and ScienceDirect until April 2024. After the search, a total of 8 studies were included, which met the needed criteria. Results: This review identified 5 conceptual approaches used to understand and assess psychological well-being in pregnant adolescents, namely (i) self-esteem, (ii) measures on anxiety, depression, emotional bonding, general positive affect, and the absence of psychological distress, (iii) discrimination experiences, self-perceptions, and social barriers experienced, (iv) positive and negative mood concepts, and (v) positive psychological functioning. The results showed that several factors were associated with psychological well-being of pregnant adolescents, including educational level, neighborhood support, financial constraints, rejection from close people, trust, and attachment with caregiver. Conclusion: This review shows the need for a more comprehensive and multidimensional approach to conceptualizing and assessing psychological well-being in pregnant adolescents. The complexity of this issue demands a thorough and inclusive approach that focuses on individual and social factors. Keywords: adolescent pregnancy; psychological well-being; adolescent growth and development